2021
DOI: 10.1371/journal.pone.0259330
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ten-eleven translocation 1 (TET1) expression as a diagnostic and prognostic biomarker of endometrial carcinoma

Abstract: Endometrial carcinoma (EC) is the most common gynecological cancer. However, there is currently no routinely used biomarker for differential diagnosis of malignant and premalignant endometrial lesions. Ten-eleven translocation (TET) proteins, especially TET1, were found to play a significant role in DNA demethylation, via conversion of 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC). TET1, 5-mC, and 5-hmC expression profiles in endometrial carcinogenesis are currently unclear. We conducted a hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
2
0
1
Order By: Relevance
“…The decreased protein expression during 72 hours of estrogen-progesterone treatment, suggests a potential aberrant regulation of TET1 in AN3 cells. Data by other studies report similar findings with decreased TET1 mRNA and protein expression in endometrial cancer tissues compared to normal ( 9 , 36 ). It has been suggested that overexpression of DNMT3a and DNMT3b contribute to hypermethylation of ERα and PR , subsequently silencing these genes in endometrial cancer ( 37 ).…”
Section: Discussionsupporting
confidence: 80%
“…The decreased protein expression during 72 hours of estrogen-progesterone treatment, suggests a potential aberrant regulation of TET1 in AN3 cells. Data by other studies report similar findings with decreased TET1 mRNA and protein expression in endometrial cancer tissues compared to normal ( 9 , 36 ). It has been suggested that overexpression of DNMT3a and DNMT3b contribute to hypermethylation of ERα and PR , subsequently silencing these genes in endometrial cancer ( 37 ).…”
Section: Discussionsupporting
confidence: 80%
“…Снижение экспрессии ТЕТ1 характерно для карциномы эндометрия, но не для предраковых заболеваний, таких как гиперплазия эндометрия. Отмечается, что высокий уровень экспрессии TET1 при раке эндометрия коррелирует с хорошими показателями выживаемости, что может быть использовано в качестве прогностического маркера [114]. Опухоли желудка также характеризуются пониженным уровнем экспрессии TET1.…”
Section: нарушения экспрессии белковunclassified
“…1,2 Global loss of 5hmC occurs in many cancers and is closely correlated with poor prognosis in multiple malignancies. 1,2,[5][6][7][8][9][10][11] These features indicate that 5hmC is a promising biomarker candidate for cancer detection.…”
Section: Introductionmentioning
confidence: 96%
“…5hmC levels are correlated with cancer initiation, progression and histological grade and negatively correlated with DNA methylation changes 1,2 . Global loss of 5hmC occurs in many cancers and is closely correlated with poor prognosis in multiple malignancies 1,2,5–11 . These features indicate that 5hmC is a promising biomarker candidate for cancer detection.…”
Section: Introductionmentioning
confidence: 99%